Auditory agnosia with anosognosia. (April 2021) - Klarendić, Maja; Gorišek, Veronika R.; Granda, Gal; Avsenik, Jernej; Zgonc, Vid; Kojović, Maja
Abstract: A 66-year-old right-handed female medical doctor suffered two consecutive cardioembolic strokes, initially affecting the right frontal lobe and the right insula, followed by a lesion in the left temporal lobe. The patient presented with distinctive phenomenology of general auditory agnosia with anosognosia for the deficit. She did not understand verbal requests and her answers to oral questions were fluent but unrelated to the topic. However, she was able to correctly answer written questions, name objects, and fluently describe their purpose, which is characteristic for verbal auditory agnosia. She was also unable to recognise environmental sounds or to recognise and repeat any melody. These inabilities represent environmental sound agnosia and amusia, respectively. Surprisingly, she was not aware of the problem, not asking any questions regarding her symptoms, and avoiding discussing her inability to understand spoken language, which is indicative of anosognosia. The deficits in our patient followed a distinct pattern of recovery. The verbal auditory agnosia was the first to resolve, followed by environmental sound agnosia. Amusia persisted the longest. The patient was clinically assessed from the first day of symptom onset and the evolution of symptoms was video documented. We give a detailed account of the patient's behaviour and provide results of audiological and neuropsychological evaluations. We discuss the anatomy of auditory agnosia and anosognosia relevant to the case. This case study may serve to better understand auditory agnosia in clinical settings. It is important to distinguish auditory agnosia from Wernicke's aphasia, because use of written language may enable normal communication.